1970
DOI: 10.3382/ps.0491280
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Phytase and Alkaline Phosphatase of Chicks: Influence of Dietary Calcium, Inorganic and Phytate Phosphorus and Vitamin D3

Abstract: A S indicated in reviews by Taylor • (1965) and Nelson (1967) data are incomplete and often conflicting in regard to the influence of dietary factors on the extent to which chicks are able to utilize phytin phosphorus. Maddaiah et al. (1964) were unable to relate supplementation with dicalcium phosphate, or calcium or sodium phytates to intestinal phytase activity in the chick or the rat. Balance studies have shown (Pileggi et al., 19SS) that in the rat high dietary Ca lowered phytate hydrolysis; vitamin D 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 19 publications
1
16
1
1
Order By: Relevance
“…If similar mechanisms were involved in preventing mineralization in the two types of experiment, this could imply that the injected phytate was converted by the recipient animal into one or more products potent as inhibitors. The enzyme phytase, which converts phytate into inositol and orthophosphate, has been demonstrated in the intestinal mucosa of the rat (Steenbock, , 1953;Pileggi, DeLuca & Steenbock, 1955) and chick (Davies, Ritcey & Motzok, 1970). Intermediate products of the action of phytase (Desjobert & Petek, 1956;Tomlinson & Ballou, 1962) and also of the acid hydrolysis of phytic acid (Desjobert & Petek, 1956;Cosgrove, 1962), include the mono-, di-, tri-, tetra-and pentaphosphate esters of inositol.…”
Section: Discussionmentioning
confidence: 97%
“…If similar mechanisms were involved in preventing mineralization in the two types of experiment, this could imply that the injected phytate was converted by the recipient animal into one or more products potent as inhibitors. The enzyme phytase, which converts phytate into inositol and orthophosphate, has been demonstrated in the intestinal mucosa of the rat (Steenbock, , 1953;Pileggi, DeLuca & Steenbock, 1955) and chick (Davies, Ritcey & Motzok, 1970). Intermediate products of the action of phytase (Desjobert & Petek, 1956;Tomlinson & Ballou, 1962) and also of the acid hydrolysis of phytic acid (Desjobert & Petek, 1956;Cosgrove, 1962), include the mono-, di-, tri-, tetra-and pentaphosphate esters of inositol.…”
Section: Discussionmentioning
confidence: 97%
“…Waldroup et al (1965) observed similar responses to higher amounts of D 3 in chicks fed on P-de cient maize-soyabean meal diets. It is well established that D3 functions not only in Pi absorption (Wasserman and Taylor, 1973) but in release of Pi from phytate (Pileggi et al, 1955;Davies et al, 1970;Mohammed et al, 1991). This probably occurs because higher doses of D3 result in increased synthesis of 1,25-dihydroxycholecalciferol, [1,25-(OH)2 D3] the active metabolite of D3.…”
Section: Discussionmentioning
confidence: 99%
“…sont susceptibles d'intervenir dans l'hydrolyse des phytates (McCuaig et Motzok, 1972 ;Davies, Ritcey et Motzok, 1970 ; Flett, 1978) et dans l'absorption du phosphore (Shirazi, Beechey et Butterworth, 1981 ; Ulmann, 1982 ;Kempson et a/., 1979 ;Birge et Avioli, 19811. Chez le rat ou le poulet, l'activité de l'une et l'autre enzymes augmente avec l'apport de vitamine D tant in vivo (Steenbock et a/., 1953 ; Pileggi, De Luca et Steenbock, 1955 ; Davies, Ritcey et Motzok, 1970 ;Roberts et Yudkins, 1961 ;Bhandari, 1980 ;Valinietse et Bauman, 1984) qu'in vitro (Peterlik et Wasserman, 1980 ;Chan et Atkins, 1983 ; Haussler, Nagode et Rasmussen, 1970 ;Bikle et al, 1979 ; Lacour, 1979). Certains auteurs (Bachelet, Lacour et Ulmann, 1982 ; Birge et Avioli, 1981) attribuent un rôle à la phosphatase alcaline dans le transport du phosphore à travers la muqueuse intestinale du fait d'une part de l'existence de substances inhibitrices communes (Haussler, Nagode et Rasmussen, 1970 ; Ulmann, 1982) (Pointillart, Fontaine et Thomasset, 1984b (Garabedian, 1984), le 25(OH)D (méthode de Preece et al, 1974).…”
Section: Introductionunclassified